EFFECT OF MATERIALISM, PUBLIC SELFCONSCIOUSNESS AND SELF-ESTEEM ON CONSPICUOUS CONSUMPTION AMONG GENERATION Z CONSUMERS - Emamdin Moustabshirah; Jugindar Singh Kartar Singh; Wong Huey Wern (International Journal of Accounting, Finance and Business, 2022)
Generation Z consumers are heading into work force and will be the primary driving force in the consumption growth of luxury products and services. However, despite a dearth of studies on the determinants of conspicuous consumption among Gen Z in Malaysia, still the effect of conspicuous consumption on materialism, public self-consciousness, and self-esteem remains unclear. This quantitative research surveyed 208 Gen Z using self-administered questionnaires in Malaysia. The philosophy of Positivism was adopted. Primary data was collected and results were scrutinized through the SPSS software that generated Descriptive and inferential statistics. Research findings revealed that materialism and self-esteem had significant impact on conspicuous consumption compared with public self-consciousness. Thus, public self-consciousness was not a significant predictor of conspicuous consumption. The research findings knowledgeably benefited retailers, marketers and advertisers who now understand better why prioritising materialism and self-esteem rather than public selfconsciousness.